The environmental factors determining temporal distributions of cetaceans in Mossel Bay, South Africa - Levy, David (Marine Research (MA-RE) Institute, 2017)
A variety of cetacean species make use of the bays along the South African coast for different purposes, including feeding, mating and calving. Sightings of five species of cetaceans were recorded from shore based locations between February 2010 and August 2014 in Mossel Bay, Western Cape. In this study, we aimed to examine the underlying environmental variables: sea surface temperature (°C), chlorophyll a concentration (mg.m-3) and moon brightness (as % of full) that potentially affect presence patterns within the bay, and several temporal scales (diurnal, monthly, seasonal, annual). The study focused on three whale species: the southern right whale (Eubalaena australis), humpback whale (Megaptera novaeangliae) and Bryde's whale (Balaenoptera brydei); and two dolphin species: the Indo- Pacific bottlenose dolphin (Tursiops aduncus), and the Indian Ocean humpback dolphin (Sousa plumbea). Generalized additive models (GAM) were used to model the sighting rate of the common cetacean species in the area, by relating sighting rate to the environmental variables. Cow-calf groups and adults-only groups were modelled separately for humpback and southern right whales. Chlorophyll a concentration is commonly indicative of high trophic productivity, and sea surface temperature is indicative of biophysical processes that influence cetacean distribution, as well as cetacean migration preferences. Change in sea surface temperature (over the study period) was a significant contributing factor to the sighting rate of cow-calf paired groups and adults-only groups of both right whales and humpback whales, underlying their greater sighting rate during the winter and spring months annually; thus, conforming to the seasonal migration from Antarctica for breeding and calving. Chlorophyll a concentration was a significant factor contributing to Bryde's whale, bottlenose and humpback dolphin distribution. These species reside along the South African coast all year round, but are more frequently seen when trophic productivity is high. During 2011, sea surface temperature values were lower and chlorophyll a concentrations greater than average in Mossel Bay, due to the La Niña effect. This was found to positively correlate with the use of Mossel Bay by the cetacean species in the area. This paper highlights the importance of biophysical processes on cetacean distribution at various temporal scales (diurnal, monthly, seasonal and annual), and the information it provides may be used for conservation planning management.